Diffusion-Weighted Magnetic Resonance Imaging: Clinical Potential and Applications - Caroli, Anna (Journal of clinical medicine, 2022)
[...]during their random, diffusion-driven displacements, water molecules microscopically probe the tissue structure, interacting with cell membranes, thus providing unique information on the tissue’s functional architecture [2]. Just as with water molecule displacements, blood flow in randomly oriented capillaries follows a random walk called pseudodiffusion. Since the pseudodiffusion coefficient (D*) is an order of magnitude higher than the water diffusion coefficient (D), true diffusion can be separated from pseudodiffusion through the use of intra-voxel incoherent motion (IVIM) models [5,6], providing information in addition to the summary ADC parameter. [...]this inter-site comparability study performed on healthy subjects reported systematic global and regional differences in common DTI outcome measures between different scanners, sequences, and processing pipelines. Since regionally inhomogeneous variations may considerably confound physiological effects and pathological changes, this paper highlights the need to harmonize DWI data acquisition and analysis to augment imaging data reliability and replicability, in particular in the context of multicenter longitudinal clinical studies, and to estimate normative values for clinical practice. [...]besides illustrating diffusion MRI’s clinical potential in both acute and chronic settings and providing an overview of possible diffusion applications in different clinical contexts, the current Special Issue also highlights cross-cutting challenges of its routine use in clinical practice for diagnosis, disease staging, disease progression monitoring, as well as for potentially guiding tailored therapy management.